The effectiveness of double incision technique in uterus preserving surgery for placenta percreta - Ibrahim Polat; Burak Yücel; Ali Gedikbasi; Halil Aslan; Aysun Fendal (BMC, 2017)
Abstract Background Placenta percreta is a life-threatening condition that places patients at risk of massive bleeding. It necessitates very complicated surgery and can result in mortality. Caesarean hysterectomy is the accepted procedure worldwide; however, recent studies discussing conservative treatment with segmental resections have been published. Foetal extraction and segmental resection can be performed through the same incision (single uterine incision) or through two different incisions (double uterine incision). In this study, we aimed to evaluate the effectiveness and results of the double incision technique. Methods Twenty-two patients with a diagnosis of placenta percreta who underwent conservative surgery were included. Segmental resection was performed via single incision in ten patients and double incision in twelve patients. Results There was no difference between the patients who underwent segmental resection via single and double incision in terms of age, gravida, number of previous caesarean deliveries, gestational age at delivery, or rate of elective surgeries. The operation time, transfusion requirement, intensive care unit admission, total hospitalization and success of conservative surgery were comparable between the groups. Conclusions Based on the outcomes of our study, double uterine incision allows for the safe extraction of the foetus during uterus-preserving surgery in patients with placenta percreta without worsening the results compared to single uterine incision. Trial registration NCT02702024 , Date of registration: February 26, 2016, retrospectively registered.